Pengaruh Employee Engagement, Work-Life Balance, Dukungan Sosial, dan Stres Kerja terhadap Kesejahteraan Psikologis Karyawan Perusahaan Garmen di Yogyakarta - Sunyoto, Danang; Mulyono, Agus (Melati Institute, 2025)
Employee psychological well-being is an important aspect in the world of work that can be influenced by various organizational and individual factors. This study aims to analyze the influence of Employee Engagement, Work-Life Balance, Social Support, and Job Stress on Employee Psychological Wellbeing at garment companies in Yogyakarta. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 850 employees of garment companies in Yogyakarta. The analysis technique used is multiple linear regression analysis to test the relationship between the independent variables (Employee Engagement, Work-Life Balance, Social Support, and Job Stress) with the dependent variable (Psychological Well-Being). The results showed that Employee Engagement, Work-Life Balance, and Social Support have a positive and significant effect on Employee Psychological Wellbeing, while Job Stress has a negative and significant effect on Employee Psychological Wellbeing. Of the four variables, Work-Life Balance has the most dominant influence in improving employee psychological well-being. These findings indicate that companies need to pay attention to work-life balance, employee engagement, and social support in the work environment, as well as manage work stress more effectively to improve employees' psychological well-being. Translated with DeepL.com (free version)